Study on Bee venom and Pain - Hyoung-Seok Yun; Young-Suk Kim; Jae-Dong Lee (Korean Pharmacopuncture Institute, 2000)
In order to study Bee venom and Pain, We searched Journals and Internet. The results were as follows: 1. The domestic papers were total 13. 4 papers were published at The journal of korean acupuncture & moxibustion society, 3 papers were published at The journal of korean oriental medical society, Each The journal of KyoungHee University Oriental Medicine and The journal of korean sports oriental medical society published 1 papers and Unpublished desertations were 3. The clinical studies were 4 and the experimental studies were 9. 2. The domestic clinical studies reported that Bee venom Herbal Acupuncture therapy was effective on HIVD, Subacute arthritis of Knee Joint and Sequale of sprain. In the domestic experimental studies, 5 were related to analgesic effect of Bee vnom and 4 were related to mechanism of analgesia. 3. The journals searched by PubMed were total 18. 5 papers were published at Pain, Each 2 papers were published at Neurosci Lett. and Br J Pharmacol, and Each Eur J Pain, J Rheumatol, Brain Res, Neuroscience, Nature and Toxicon et al published 1 paper. 4. In the journals searched by PubMed, Only the experimental studies were existed. 8 papers used Bee Venom as pain induction substance and 1 paper was related to analgesic effects of Bee venom. 5. 15 webpage were searched by internet related to Bee Venom and pain. 11 were the introduction related to arthritis, 1 was the advertisement, 1 was the patient's experience, 1 was the case report on RA, 1 was review article.